Stepwise deactivation of gibberellins during rice internode elongation - Toshiaki Ishida; Yingying Zhang; Hongbo Zhu; Shoko Fudano; Yu Peng; Yoshiya Seto; Kiyoshi Mashiguchi; Jiyun Liu; Zuhua He; Shubiao Zhang; Shinjiro Yamaguchi (Proceedings of the National Academy of Sciences, 2025)
Bioactive gibberellins (GAs) are a class of plant hormones that regulate various aspects of plant growth and development, and several key GA deactivation enzymes have been identified. In rice, non-13-hydroxylated GAs have been shown to be deactivated via 16α,17-epoxidation by a cytochrome P450 monooxygenase, ELONGATED UPPERMOST INTERNODE (EUI/CYP714D1). Although 16,17-dihydro-16α,17-epoxyGA 4 (16α,17-epoxyGA 4 ), the product of EUI from bioactive GA 4 , has shown weak bioactivity on rice seedlings, how 16α,17-epoxyGAs are further deactivated remains elusive. Here, we identify the EUI2 gene, which regulates internode elongation in rice, using a map-based cloning strategy. EUI2 encodes an epoxide hydrolase that hydrolyzes 16α,17-epoxyGAs to 16,17-dihydro-16α,17-dihydroxyGAs. The eui2 mutants are taller than wild-type plants but are shorter than the eui mutants. However, the levels of known bioactive GAs in the uppermost internodes are not significantly increased in the eui2 mutants. Instead, we show that the eui2 mutants accumulate 16α,17-epoxyGA 4 to high levels. We also show that exogenously applied 16α,17-epoxyGA 4 is significantly active in elongating the uppermost internode, although not as potent as GA 4 . Furthermore, we demonstrate that 16α,17-epoxyGA 4 can directly interact with the rice GA receptor, GIBBERELLIN INSENSITIVE DWARF1, in vitro. Taken together, the sequential action of EUI and EUI2 results in the stepwise deactivation of GAs during internode elongation in rice. Our data also suggest that the accumulation of a weakly active GA contributes to the mildly tall phenotype of the eui2 mutants.